Permutations of responsibility in international law - Pazartzis, Photini; Merkouris, Panos (Queen Mary studies in international law, 2019)
In 'Permutations of Responsibility in International Law' the concept of responsibility in international law is tackled from a multitude of angles. The various contributions, which emerged from the proceedings of the ILA Hellenic Branch Regional Conference (2012), examine both classical and modern issues relating to the nature of responsibility, both as responsibility for unlawful acts and liability for lawful acts, the multifariousness of actors whose actions (or omissions) may give rise to responsibility and finally the plethora of responsibility-related issues that have emerged in different areas of international law, be it international law of the sea, trade and investment or human rights law.